Risda Semaian dan Landskap Sdn Bhd: Risda Semaian Sarawak - Mustapha Kamal, Abdul Rasyid (Universiti Teknologi MARA, Sarawak, 2016)
RISDA Semaian & Landskap Sdn Bhd or as known as RISDA Semaian established on 31th July 1979 and fully owned by RISDA, government agencies that responsible to ensure smallholder sector successfully accomplished under Kementerian Kemajuan Luarbandar can Wilayah (KKLW). Risda Semaian with a Bumiputra status start established for preparing and become supplier of rubber and oil palm seeds to smallholder that joining RISDA programme. In other word, it’s developing Malaysia's smallholder rubber and Oil Palm Industry by producing and supplying high quality rubber and oil palm seedlings. Back more than 20 nurseries all over Malaysia RSSB have managed to position itself as an effective force rival ring. Through its relentless effort in developing the smallholders sector, RSSB has become the biggest rubber seedlings producers as well as strong and reliable producer oil palms for local and worldwide consumption.